Characteristics of Resection Parameters in Robot‐Assisted Total Knee Arthroplasty With the Ligament Balancing Workflow - Qing‐Da Wei; Hao‐Ming An; Wang Gu; Wei Sun; Rui Li; Wei Chai (Orthopaedic Surgery)
ABSTRACT Objective Robotic‐assisted total knee arthroplasty (TKA) is a novel orthopedic technique. The workflow of robotic‐assisted TKA is quite different from that of traditional manual TKA and may result incompletely different resection parameters. Understanding these parameters may help surgeons better perform robotic‐assisted TKA. This study aims to analyze the specific resection parameters of robotic‐assisted TKA. Methods We retrospectively reviewed 85 MAKO‐assisted TKA surgeries performed by three surgeons at our institution between May 2021 and November 2023. All patients had unilateral primary knee arthritis, and a Triathlon PS (Stryker) knee prosthesis was used. Intraoperative resection plan, radiological outcomes, and clinical outcomes were collected among them. The angle between the transepicondylar axis (TEA) and the femoral prosthesis axis was defined as rTEA, the angle between the posterior condylar axis (PCA) and the femoral prosthesis axis was defined as rPCA. The t‐test and the Chi‐square test (or Fisher's exact probability test) were used to determine differences in categorical variables. Results rTEA averaged 2.7° (range, 0°–6.7°), and rPCA averaged 4.9° (range, 0.2°–9.6°). The mean resection of the medial distal femur was 7.7 mm (range, 3.0–12.5), that of the lateral tibial plateau was 6.4 mm (range, 1.5–13.0), and that of the medial posterior condyle of the femur was 10.6 mm (range, 6.5–17.5), whereas that of the lateral posterior condyle of the femur was 6.7 mm (range, 2.0–13.0). Conclusion Robotic‐assisted TKA using the ligament balancing workflow generally resulted in greater external rotation than reported reference values for conventional manual TKA within the existing literature, with reference to both the TEA and PCA. In addition, tibial resection was generally less, and the joint line was generally shifted upwards.